Enhancing Basic Communication Skills of Children with Autism Spectrum Disorder through the TEACCH Method and Teacher-Parent Collaboration - Resta Rayanda; Oom Sitti Homdijah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to optimize the fundamental communication capacity of students with Autism Spectrum Disorder (ASD) by utilizing the Treatment and Education of Autistic and related Communication-Disabilities (TEACCH) framework, combined with teacher-parent collaboration. The study used a mixed-method approach with a one-group pretest–posttest design. The research subjects consisted of four children with ASD, four parents, and one autistic class teacher as the main facilitator. Participants in this study consisted of two main groups, namely children with ASD and their parents. The study focused on four first-grade students. The participant selection process used purposive sampling techniques. To obtain comprehensive and valid data, this study used several complementary data collection instruments, namely an ASD communication skills observation guide for Children with ASD, interview protocols for teachers and parents, and semi-structured interviews with open-ended questions. Data analysis was conducted in an integrated manner by combining qualitative and quantitative approaches. The results showed an average increase of 34% in children's basic communication skills, particularly in recognizing themselves, family members, and classmates, as well as in expressing their needs or appropriately rejecting something.